2022
DOI: 10.3390/cancers14153840
|View full text |Cite
|
Sign up to set email alerts
|

Theranostics Using Indocyanine Green Lactosomes

Abstract: Lactosomes™ are biocompatible nanoparticles that can be used for cancer tissue imaging and drug delivery. Lactosomes are polymeric micelles formed by the self-assembly of biodegradable amphiphilic block copolymers composed of hydrophilic polysarcosine and hydrophobic poly-L-lactic acid chains. The particle size can be controlled in the range of 20 to 100 nm. Lactosomes can also be loaded with hydrophobic imaging probes and photosensitizers, such as indocyanine green. Indocyanine green-loaded lactosomes are sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The near-infrared fluorescent protein 713 (iRFP713) has an excitation and emission wavelength at 690 nm and 713 nm, respectively, making it an optimal option for mammalian tissue imaging 18 . While near-infrared fluorescent dyes like 5-aminolevulinic acid 27 , fluorescein sodium 28 , and indocyanine green 29 have been widely used to determine the surgical margins of cancer tissues, they are unable to effectively display molecular status in cancer cells. By fusing double ERE and double PRE, we formed an ER/PR response element that can efficiently detect both proteins in breast cancer cells, activating the expression of iRFP713 and allowing cancer cells to display red light under near-infrared laser (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The near-infrared fluorescent protein 713 (iRFP713) has an excitation and emission wavelength at 690 nm and 713 nm, respectively, making it an optimal option for mammalian tissue imaging 18 . While near-infrared fluorescent dyes like 5-aminolevulinic acid 27 , fluorescein sodium 28 , and indocyanine green 29 have been widely used to determine the surgical margins of cancer tissues, they are unable to effectively display molecular status in cancer cells. By fusing double ERE and double PRE, we formed an ER/PR response element that can efficiently detect both proteins in breast cancer cells, activating the expression of iRFP713 and allowing cancer cells to display red light under near-infrared laser (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, researchers have also discovered its potential for PDT applications. ICG has shown efficacy in both in vitro and in vivo experiments, showing its potential for imaging and treating malignant tumors simultaneously ( 79 ). Porphysomes, another example of dual-function PSs, are self-assembled porphyrin-lipid nanoparticles.…”
Section: Advanced Pss For Pdtmentioning
confidence: 99%
“…18 PSar is characterized by becoming hydrophilic upon hydration in an aqueous solvent and shows good stealth ability on drug delivery carriers. [19][20][21][22][23][24] Hence, this present study focused on exploiting the natural and simplest polypeptoid, PSar, in developing a temperature-responsive bio-based polymer.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 We have previously reported that an amphiphilic block-co-polypeptide composed of a hydrophilic PSar chain and a hydrophobic α-helical block (L-Leu-Aib) 6 , which consists of alternating sequences of leucine (Leu) and 2-aminoisobutyric acid (Aib), forms nanotubes with uniform diameters. [19][20][21][22][23][24][25][26] In the hydrophobic phase of the nanotube assembly, precise protein-like orientations of the helices are induced by interlocking of the irregularities created by the helix side chains. The assembly shows helix orientation-derived anisotropy and curvature, leading to well-defined nanotubes.…”
Section: Introductionmentioning
confidence: 99%